Dasatinib inhibits peripapillary scleral myofibroblast differentiation. (May 2020) - Chow, Amanda; McCrea, Liam; Kimball, Elizabeth; Schaub, Julie; Quigley, Harry; Pitha, Ian
Abstract: Scleral fibroblast activation occurs in glaucomatous and myopic eyes. Here we perform an unbiased screen to identify kinase inhibitors that reduce fibroblast activation to diverse stimuli in vitro and to in vivo intraocular pressure (IOP) elevation. Primary cultures of peripapillary scleral (PPS) fibroblasts from two human donors were screened using a library of 80 kinase inhibitors to identify compounds that inhibit TGFβ-induced extracellular matrix (ECM) synthesis. Inhibition of myofibroblast differentiation was verified by alpha smooth muscle actin (αSMA) immunoblot and collagen contraction assay. Inhibition of IOP-induced scleral fibroblast proliferation was assessed by ELISA assay for proliferating cell nuclear antigen (PCNA). The initial screen identified 7 inhibitors as showing>80% reduction in ECM binding. Three kinase inhibitors were verified to reduce TGFβ-induced αSMA expression and cellular contractility (rottlerin, PP2, tyrphostin 9). The effect of three Src inhibitors, bosutinib, dasatinib, and SU-6656, on myofibroblast differentiation was evaluated, with only dasatinib significantly inhibiting TGFβ-induced ECM synthesis, αSMA expression, and cellular contractility at nanomolar dosages. Subconjunctival injection of dasatinib reduced IOP-induced scleral fibroblast proliferation compared to control (4.9 ± 11.1 ng/sclera with 0.1 μM versus 88.7 ± 38.6 ng/sclera in control, P  < 0.0001). Dasatinib inhibits scleral myofibroblast differentiation and there is pharmacologic evidence that this inhibition is not solely due to Src-kinase inhibition. Highlights: Scleral biomechanics and collagen ultrastructure are altered in glaucoma. We performed a screen to identify kinase inhibitors that reduce scleral myofibroblast differentiation. The multikinase inhibitor dasatinib reduces scleral myofibroblasts at nanomolar dosages.